2018
DOI: 10.1016/j.cpr.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Do guided internet-based interventions result in clinically relevant changes for patients with depression? An individual participant data meta-analysis

Abstract: Little is known about clinically relevant changes in guided Internet-based interventions for depression. Moreover, methodological and power limitations preclude the identification of patients' groups that may benefit more from these interventions. This study aimed to investigate response rates, remission rates, and their moderators in randomized controlled trials (RCTs) comparing the effect of guided Internet-based interventions for adult depression to control groups using an individual patient data meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
185
4
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 273 publications
(228 citation statements)
references
References 110 publications
25
185
4
8
Order By: Relevance
“…Potential advantages include efficacy, low‐threshold availability, flexibility, low cost, and low clinician burden. Meta‐analyses have shown that eCBT Internet interventions for depression are effective in the general population, on average, and certain clinician‐supported forms of eCBT have been shown to be as effective as face‐to‐face psychotherapy, which suggests that these interventions might be effective for PwE as well …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential advantages include efficacy, low‐threshold availability, flexibility, low cost, and low clinician burden. Meta‐analyses have shown that eCBT Internet interventions for depression are effective in the general population, on average, and certain clinician‐supported forms of eCBT have been shown to be as effective as face‐to‐face psychotherapy, which suggests that these interventions might be effective for PwE as well …”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses have shown that eCBT Internet interventions for depression are effective in the general population, on average, and certain clinician-supported forms of eCBT have been shown to be as effective as face-to-face psychotherapy, which suggests that these interventions might be effective for PwE as well. 9,10 Despite these advantages and encouraging findings, several limitations of eCBT must also be considered, including concerns about data security, incapacity to respond to crises, low adherence, and potential lack of safety and efficacy. For example, the effects of some fully automated eCBT interventions are only modest, although providing clinician support may improve adherence and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in offering internet-based interventions as a way of improving access to psychological treatments in the primary care population, for example, in the United Kingdom (Richards et al, 2018). Therapist-guided internet-based treatments result in large and clinically relevant improvements on depression in clinical trials (Karyotaki et al, 2018) and other conditions (Andersson, Cuijpers, Carlbring, Riper, & Hedman, 2014) and have shown effectiveness for several conditions when implemented in routine care (Andersson & Hedman, 2013;Hedman et al, 2014;Nordgreen, Gjestad, Andersson, Carlbring, & Havik, 2018;Titov et al, 2017).…”
Section: Internet-based Psychological Treatmentsmentioning
confidence: 99%
“…Evidence is accumulating for the efficacy of internet‐based cognitive behavioral treatments (iCBT; Andersson et al, 2013; Andrews, Cuijpers, Craske, McEvoy, & Titov, 2010; Cuijpers, Donker, Van Straten, Li, & Andersson, 2010; Spek et al, 2007; Wagner, Horn, & Maercker, 2014; Wright et al, 2005). Especially when provided with the help of a coach, guided iCBT consistently outperforms waitlist conditions and appears to achieve levels of efficacy similar to face‐to‐face CBT (Andersson & Cuijpers, 2009; Andrews et al, 2018; Cuijpers, Donker, van Straten, Li, & Andersson, 2010; Gellatly et al, 2007; Karyotaki et al, 2018; Richards & Richardson, 2012; Spek et al, 2007). Much less is known about the long‐term effects of guided iCBT programs.…”
Section: Introductionmentioning
confidence: 98%